The Development of Creative Economy Research in Southeast Asia Based on Bibliometric Analysis and Thematic Trends 2013–2024 - Loso Judijanto (West Science Journal Economic and Entrepreneurship, 2026)
The creative economy has become a strategic sector in economic development in various Southeast Asian countries due to its contribution to innovation, job creation, and strengthening cultural identity. As academic attention to this topic increases, scientific mapping is needed to understand research developments, collaboration patterns, and emerging thematic trends in the literature. This study aims to analyze the development of research on the creative economy in Southeast Asia during the period 2013–2024 using a bibliometric approach. Research data was obtained from the Scopus database and analyzed using VOSviewer software to map the collaboration network of authors, institutions, countries, and the emergence of research keywords. The analysis results show that research on the creative economy in Southeast Asia has experienced a significant increase, with a primary focus on the theme of economic development, which is closely related to topics such as sustainability, commerce, finance, policymaking, and cultural industries. Visualization of the collaboration network indicates the existence of collaboration.Cross-border research, particularly between Southeast Asian and European countries, is also being conducted, although collaboration remains relatively limited. Thematic trend analysis also indicates a shift in research focus from economic development to more specific issues such as creative industry competitiveness, public policy, and the development of creative subsectors such as animation and cultural industries. The findings of this study provide a comprehensive overview of the dynamics of creative economy research in Southeast Asia and open up opportunities for further, more in-depth research on digital transformation, creative entrepreneurship, and regional economic integration to support future creative economy development.